2006
DOI: 10.1172/jci27955
|View full text |Cite
|
Sign up to set email alerts
|

PPAR : a dagger in the heart of the metabolic syndrome

Abstract: Obesity is a growing threat to global health by virtue of its association with insulin resistance, glucose intolerance, hypertension, and dyslipidemia, collectively known as the metabolic syndrome or syndrome X. The nuclear receptors PPARα and PPARγ are therapeutic targets for hypertriglyceridemia and insulin resistance, respectively, and drugs that modulate these receptors are currently in clinical use. More recent work on the less-described PPAR isotype PPARδ has uncovered a dual benefit for both hypertrigly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
418
2
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 589 publications
(440 citation statements)
references
References 92 publications
8
418
2
12
Order By: Relevance
“…As a nuclear receptor involved in multiple physiological regulations (Cheng et al, 2004;Kim et al, 2004;Piqueras et al, 2007), PPAR-b is an ideal drug target for the treatment of diseases. Studies have shown a wide range of PPAR-b agonists, including eicosanoids, fatty acids and some synthetic compounds (for example, GW501516); GW501516 is currently in a phase II clinical trial for dyslipidemia (Barish et al, 2006;Peraza et al, 2006;Takahashi et al, 2006). Because of its protective role in the carcinogenesis and progression of colon cancer as suggested in this study, PPAR-b may be a potential drug target for colon cancer.…”
Section: Studies Have Identified Ilk As a Direct Target Of Ppar-b (mentioning
confidence: 82%
“…As a nuclear receptor involved in multiple physiological regulations (Cheng et al, 2004;Kim et al, 2004;Piqueras et al, 2007), PPAR-b is an ideal drug target for the treatment of diseases. Studies have shown a wide range of PPAR-b agonists, including eicosanoids, fatty acids and some synthetic compounds (for example, GW501516); GW501516 is currently in a phase II clinical trial for dyslipidemia (Barish et al, 2006;Peraza et al, 2006;Takahashi et al, 2006). Because of its protective role in the carcinogenesis and progression of colon cancer as suggested in this study, PPAR-b may be a potential drug target for colon cancer.…”
Section: Studies Have Identified Ilk As a Direct Target Of Ppar-b (mentioning
confidence: 82%
“…In recent years PPARδ has emerged as a key protein in the regulation of energy metabolism by its ability to enhance fatty acid catabolism, energy uncoupling and insulin sensitivity in the liver, adipose tissue and skeletal muscle [6][7][8][9][10]36].…”
Section: Discussionmentioning
confidence: 99%
“…To address these impacts, public health awareness of meal choices and portions, and physical exercise are foremost. However, for those already affected and refractory to diet and exercise changes, pharmacologic modification of metabolism provides an opportunity to prevent mortality and morbidity associated with diabetes, cardiovascular disease and the metabolic syndrome Barish et al 2006).…”
Section: Metabolic Control By Nrsmentioning
confidence: 99%
“…Overexpression of VP16-PPARδ in skeletal muscle has profound effects, converting untrained animals into "marathon mice" with a substantial conversion of muscle to a slow-twitch form . While genetic introduction of VP16-PPARδ presents an extreme case, some components of this phenotype are reiterated by ligand treatments and exercise that hint at effective treatments for metabolic syndrome mediated by PPARδ Barish et al 2006). For instance, patients with poor responsiveness to exercise and dietary changes may benefit from a 'jump start' in the form of PPAR agonists.…”
Section: Pparmentioning
confidence: 99%